The Internationalization of Services: Examining of An Aspect of International Marketing for Realeyes LTD - Bettadapura Keshavamurthy, Sharath Kumar (2009)
This report focuses fundamentally on one particular aspect of the International Marketing Plan prepared for Realeyes Data Services Ltd, i.e. Internationalisation of services. Realeyes is a UK-based SME registered in London, founded few years ago by three entrepreneurs Niall, Mihkel and Elnar (Oxford alumni) with established presence in countries like US, Poland and Ukraine and looking to launch in Australia. The paper also achieves this by elaborating on the B2B context to which internationalisation applies, globalisations of an SME like Realeyes in its potential and ability to globalise its data services-offering. Research methodologies include secondary research from academic papers, Journals, World-Wide Web. Also, some Interviews and survey data obtained for group report (marketing-plan) are adapted in this work, in order to highlight the empirical finding of internationalisation of Services through primary research. The analysis includes internationalisation stages, modes and patterns which help to explore strategic options based on Internationalisation theories. These theories include Uppsala model (Staged approach), Network theories and the Eclectic theory. Localisation challenges are also explained, keeping in mind the offering of bespoke services and location-based services in contrast. Entry-mode options and need for partnerships are examined, while, importance of partner-profiling is discussed. A concise account of the effect of internationalisation of Realeyes as an organisation is produced. An attempt to discuss barriers and risks encountered by a firm in its international Marketing of services is made, while looking at SME risk and cultural issue management. A brief account is also given of International trade and policies to be considered while internationalising, before finishing with a qualified conclusion that Realeyes’ internationalisation process tends to follow an integrated, dynamic strategy in its service-globalising process. The firm is recommended to maintain its business network relationships and organisational learning, while build its image by nurturing & communicating its uniqueness of offerings to sustain its international competitive advantage. Realeyes’ forging relationships with its key stakeholders, especially supplier and government are important. International marketing involves costs, hence Realeyes is recommended to use social media and existing networks to offset financial and human capital constraints, while looking at memberships with web-based B2B associations and enlist themselves for trade–events so that they are visible to international audience.